الصراع التنظيمي كمتغير وسيط في العلاقة بين سمات القائد وشعور العاملين بالبنوك الحكومية بالاغتراب الوظيفي - سقراط، رانيا علي محمد عبده; حمادة، حسام أحمد علي أحمد; عبدالدايم، وائل محمود محمد (المجلة العلمية للدراسات والبحوث المالية والتجارية: علمية محكمة., 2025)
This study aims to examine the effect of leader characteristics on government bank employees’ feelings of job alienation, through organizational conflict as a mediating variable. the researchers used the descriptive analytical method by applying it to a sample of (450) employees working in government banks across different managerial levels. the results showed that there is a significant effect of leader traits on both organizational conflict and feelings of job alienation among employees, and that organizational conflict has an influential role in increasing the level of feelings of job alienation among employees, and that organizational conflict plays a mediating role in the relationship between leader traits and employees’ feelings of job alienation. considering the results of the study; a set of recommendations have been proposed that can contribute to utilize positive characteristics of the leader in reducing the levels of feelings of job alienation among employees. يهدف هذا البحث إلى دراسة تأثير سمات القائد على شعور العاملين بالبنوك الحكومية بالاغتراب الوظيفي، من خلال الصراع التنظيمي كمتغير وسيط. ولقد استخدم الباحثون المنهج الوصفي التحليلي من خلال التطبيق على عينة قوامها (450) موظفا يعملون في البنوك الحكومية عبر مستويات إدارية مختلفة. وقد أظهرت نتائج الدراسة وجود تأثير معنوي لسمات القائد على كل من الصراع التنظيمي ومشاعر الاغتراب الوظيفي لدى العاملين، وأن الصراع التنظيمي له دورا مؤثرا في زيادة مستوى الشعور بالاغتراب الوظيفي لدى العاملين، وأن الصراع التنظيمي يلعب دور الوساطة الجزئية في العلاقة بين سمات القائد وشعور العاملين بالاغتراب الوظيفي. وفي ضوء ما أسفرت عنه الدراسة من نتائج؛ فقد اقترحت مجموعة من التوصيات التي يمكن أن تسهم في الاستفادة من السمات الإيجابية للقائد في التقليل من مستويات الشعور بالاغتراب الوظيفي لدى العاملين.